Chicken Feather Waste Valorization Into Nutritive Protein Hydrolysate: Role of Novel Thermostable Keratinase From Bacillus pacificus RSA27 - Sharma, Chhavi; Timorshina, Svetlana; Osmolovskiy, Alexander; Misri, Jyoti; Singh, Rajni (Frontiers in Microbiology, 2022)
Microbial keratinases exhibit a momentous role in converting keratin biowastes into exceedingly valuable protein supplements. This study reports a novel, highly stable keratinase from Bacillus pacificus RSA27 for the production of pure peptides rich in essential amino acids from chicken feathers. Purified keratinase showed a specific activity of 38.73 U/mg, 2.58-fold purification, and molecular weight of 36 kDa. Kinetic studies using a chicken feather as substrate report Km and Vmax values of 5.69 mg/ml and 142.40 μg/ml/min, respectively, suggesting significant enzyme-substrate affinity/biocatalysis. Identification and in silico structural-functional analysis of keratinase discovered the presence of distinct amino acid residues and their positions. Besides, keratinase possesses a high-affinity calcium-binding site (Asp128, Leu162, Asn164, Ile166, and Val168) and a catalytic triad of Asp119, His151, and Ser308, known attributes of serine protease (subtilisin family). Furthermore, a scale-up to 5 L fermenter revealed complete feather hydrolysis (94.5%) within 24 h with high activity (789 U/ml) and total amino acid of 153.97 μmol/ml. Finally, cytotoxicity evaluation of protein hydrolysate resulted in negligible cytotoxic effects (1.02%) on the mammalian hepatoblastoma cell line, signifying its potential biotechnological applications.